Integration Of Legal Education As A Preventif Measure Againts Sexual Harassement Of Minors - Muyasir, Dean Hasan; budimansyah, Dasim; Sartika, Rika (Res Nullius Law Journal, 2025)
Crimes against minors involving sexual abuse occur due to environmental factors and relationships that are not controlled by parents. This is an important issue that parents have an important role in educating and keeping their children under constant supervision. This research aims to determine the factors that cause minors to commit crimes of sexual harassment and murder of junior high school girls under the age of 16 years committed by 3 men of the same age when they committed the rape after the victim was murdered and to find out how effective rehabilitation policies are in dealing with crimes against minors. . This research method uses qualitative data collection through interviews with lecturers who are experts in public policy, criminal law and collecting secondary data through literature studies by analyzing articles to find data and findings from previous researchers. On the other hand, the factor causing this problem is caused by adult viewing, so the perpetrator tends to have the curiosity to commit sexual crimes against the victim. The implications of this research provide learning to the general public, in particular the need to supervise children to be wiser in knowing their social environment as well as providing additional education such as legal and sexual education, this can prevent children from committing deviations from norms that conflict with and emphasize rehabilitation policies.